PSYCHOSOCIAL CARE PROFESSIONALS’ CONCEPTIONS ON SOCIAL INCLUSION - Elisângela Braga de Azevedo; Rafael Nicolau Carvalho; Renata Cavalcanti Cordeiro; Camilla de Sena Guerra; Lawrencita Limeira Espinola; Maria de Oliveira Ferreira Filha (Cogitare Enfermagem, 2013)
This study aimed to investigate the conceptions on Social Inclusion held by professionals who work in psychosocial care in Campina Grande in the state of Paraíba. It is descriptive-interpretive and qualitative research, undertaken between June and July 2010 with 19 professionals. Semi-structured interviews were used for production of the empirical material and content analysis as the technique for analysis. It was perceived that the professionals have a conception of Social Inclusion which is associated with the paradigm of rehabilitation/re-insertion, showing that the service users need to be rescued and re-inserted into co-existence with the community and with the social groups in order to recognized as citizens. The participants refer to social inclusion as a possibility for access/accessibility in social environments, imprinting, in their discourses, the need for inclusion of these in educational experiences, leisure and shopping, among others. The professionals fulfil their role in the context of the Psychiatric Reform, promoting mental health based on social insertion.DESCRIPTORS: Mental health; Mental health services; Health profession